Managing Co‐creation Design: A Strategic Approach to Innovation. (22nd January 2015) - Frow, Pennie; Nenonen, Suvi; Payne, Adrian; Storbacka, Kaj
<x xml:space="preserve">Abstract</x> Co‐creation offers firms and their network of actors significant opportunities for innovation, as each actor offers access to new resources through a process of resource integration. However, despite the significant advantages that co‐creation can offer, there is surprisingly little research providing a strategic approach for identifying the most advantageous co‐creation opportunities, especially when many possible options are available. Recently, scholars have called for research that develops tools and processes related to co‐creation. This study addresses these priorities, making two contributions. First, in contrast to previous work considering co‐creation more generally, or focusing on one specific form only, e.g. co‐production, this paper offers a detailed and granular approach to co‐creation design. A co‐creation design framework is developed, which incorporates multiple design dimensions and categories that can reveal new co‐creation opportunities. Second, the research extends the application of a design approach, specifically within the context of co‐creative activities. The authors use field‐based research with senior executives to develop a framework that includes key co‐creation design elements. A morphological approach is used to explore how a lead firm can identify attractive co‐creation opportunities. An innovation solution in one organization provides an illustration of how the co‐creation design framework can be applied.